2018
DOI: 10.1371/journal.pone.0202959
|View full text |Cite
|
Sign up to set email alerts
|

The association between MTHFR gene polymorphisms (C677T, A1298C) and oral squamous cell carcinoma: A systematic review and meta-analysis

Abstract: A consensus has not been reached regarding the association of MTHFR gene polymorphism and susceptibility to oral squamous cell carcinoma (OSCC). We performed a meta-analysis to better evaluate the association between MTHFR C677T, A1298C polymorphism and OSCC risk. The studies regarding the association of MTHFR C677T, A1298C polymorphisms and OSCC were identified in PubMed and EMBASE and Google Scholar. The pooled odd rates (ORs) with 95%CIs were estimated using a fixed-effect or random-effect model. The associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It was found that MTHFD is irreversibly converted to 5-MeTHF in the intracellular folate metabolism and methionine-homocysteine cycle by the critical enzyme MTHFR [25]. A meta-analysis revealed a statistically significant connection between MTHFR gene polymorphisms and the risk of developing OSCC [26]. is indicates that MTHFD family genes promote cancer progression through interacting with other metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that MTHFD is irreversibly converted to 5-MeTHF in the intracellular folate metabolism and methionine-homocysteine cycle by the critical enzyme MTHFR [25]. A meta-analysis revealed a statistically significant connection between MTHFR gene polymorphisms and the risk of developing OSCC [26]. is indicates that MTHFD family genes promote cancer progression through interacting with other metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…While we expected to observe a more profound difference between our DF and SF groups, it is conceivable that environmental factors, like diet, must interact with genetics to observe an effect. For example, polymorphisms in the gene for methylenetetrahydrofolate reductase, encoded by MTHFR, are clearly linked to increased risk of oral SCC, as illuminated by a meta‐analysis of 13 human studies involving data from 1539 oral SCC patients and 2131 controls (Ge et al, 2018). They found that the T allele, and in particular the TT genotype, of MTHFR C677T polymorphism was linked to increased risk of oral SCC.…”
Section: Discussionmentioning
confidence: 99%
“…The T allele and the TT genotype have been associated with other oral disease contexts, including lichen planus and squamous cell carcinoma. 29,30 The enzyme encoded by this gene participates in the folate metabolism pathway, which produces the SAM radicals used by the DNMTs as methyl donors for DNA methylation. Marinho, et al 32 (2019).…”
Section: Methylation Profile Analysismentioning
confidence: 99%